TAX AWARENESS: FACTORS INFLUENCING STUDENT INTEREST TO PARTICIPATE IN TAX BREVET TRAINING (ISLAMIC ECONOMIC PERSPECTIVE) - Inayah, Nindyah Lutfi Nur; Auliyah, Iriana; Agit, Alamsyah (MUAMALATUNA, 2024)
This research seeks to investigate the elements that determine student interest in tax brevet training, particularly from an Islamic economic perspective. It examines how quality motivation, educational expense perceptions, and career incentive affect student engagement in such training programs. This research uses a quantitative methodology to examine student interest in tax brevet training from an Islamic economic perspective. Students interested in tax brevet training programs are surveyed for the study. The survey questions examine how quality motivation, educational expense perception, and career motivation affect their interest in such training. This study found that quality motivation strongly affects student interest in tax brevet training, suggesting that perceived quality and benefits motivate participation. Perceptions of educational expense and professional incentive do not affect student interest.